Anhedonia reduction correlates with increased ventral caudate connectivity with superior frontal gyrus in depression. (July 2022) - Yang, Xinhua; Huang, Jia; Roser, Matthew E.; Xie, Guangrong
Abstract: This study was to investigate the relationship between the ventral caudate connectivity and anhedonia. Nineteen depressed patients and 16 healthy controls participated in two identical functional magnetic resonance imaging scans during a 1-year period to determine the resting-state functional connectivity changes using a seed-based approach. Patients showed increased left ventral caudate functional connectivity with superior frontal gyrus over time and the increased connectivity was associated with anhedonia improvement. None of these associations were observed in healthy controls. The findings suggest that left ventral caudate may serve as a potential target to improve the severity of anhedonia. Highlights: The relationship between brain functional connectivity and anhedonia reduction was investigated. Increased left ventral caudate connectivity with bilateral superior frontal gyrus was found over time. The increased ventral caudate-prefrontal connectivity was associated with anhedonia reduction.